Improvement of special physical training of female gymnasts in sports aerobics at the stage of preliminary basic training - Galyna Artemyeva; Tetiana Moshenska (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to investigate the influence of the proposed methodology on the indicators of special physical preparedness of female gymnasts in sports aerobics at the stage of preliminary basic training. Material & Methods: in the study took part girls 7-9 years in the number of 20 athletes 1st and 2 nd junior category in sports aerobics. The control group consisted of 10 people and the experimental group consisted of 10 people. To conduct our research, we used the following methods: analysis of scientific and methodological literature, pedagogical observations, pedagogical testing, pedagogical experiment, method of peer review, methods of mathematical statistics. Results: as a result of the study, a positive effect of the means of gymnastic exercises without a subject and with the subject on the indices of special physical preparedness of female gymnasts in sports aerobics at the stage of preliminary basic training. Conclusion: five out of six indicators of special physical readiness have been significantly changed at a given reliability 95%.